How to Promote Intercultural Awareness in the Classroom Through Teaching Vocabulary in Kindergarten 5 at UPB School? (2018)
ABSTRACT: This action-research project pointed at identifying what boys and girls from the kindergarten of a private institution in Medellin make of the creation of intercultural awareness, about their own culture and that pertaining to others, through the use of vocabulary for its fostering in the English class. Interculturality is understood as a dimension where the diversity of people and groups is met and embraced. In carrying out this project, the following data collection methods were used: observations, interviews and questionnaires. The analysis of these data led to the conclusion that the boys and girls understood that there are cultural aspects from other parts of the world that enrich our own culture, with regard to the differences in the language we speak, the garments we wear, the seasons throughout a year and the traditional dishes that identify among others.